Prevulcanização do látex natural extraído da hancornia speciosa gomes (Mangabeira) e da hevea brasiliensis (seringueira) - Gomes, Willian Pereira [UNESP] (2013)
Natural rubber is one of the most consumed polymer in the worldwide and pneumatic industry is responsible for approximately three fourths of total consumption. Hevea brasiliensis is the most important producer of natural rubber, being responsible for 99% of global production. The Hancornia speciosa Gomes is also produces white latex that can be tapped from the tree similarly to Hevea. Although it has been used commercially in emergency periods, nowadays Hancornia rubber has no technology use due to its low production and rubber quality. The latex blend can be a viable alternative to the use of mangabeira latex as one additional income besides of fruit commercialization. In this sense, the proposal of this work was to evaluate the influence of prevulcanization condition in the Hancornia speciosa Gomes (mangabeira) and Hevea brasiliensis (seringueira) latexes and also in its mixture, on the rubber proprieties. The latexes were prevulcanizated by conventional (CV), semi-efficient (SEV) and efficient (EV) vulcanization systems under temperatures of 60, 70 and 80 ° C. The crosslinked quantity was investigated by the swelling technique and the mechanical proprieties were obtained from tensile experiments and shore A hardness. The results showed that the quantity of crosslinked, stress at break and shore hardness are dependent of prevulcanization condition. The values of these proprieties found for mangabeira rubber were lower than the values found for the seringueira rubber. The highest stress at break, shore hardness and strain to seringueira and mangabeira rubber were obtained using the CV and SEV systems, respectively, under temperature of 80° C for 3 hours. Theses value are: 22 MPa, 42 shore A and 895% that are around 150%, 68% e 25%, respectively, higher than found to mangabeira rubber (8,8 MPa, 25 Shore A and 714%). The rubbers obtained from mixture of latex have the mechanical proprieties closed to the seringueira rubber for blends ...